Personal income tax payment system in Malaysia schedular tax deduction scheme - Tayib, Mahamad; Yusof, Rohana @ Norliza; Mansor, Muzainah (Universiti Utara Malaysia, 2009)
Personal Income Tax Payment Systemin Malaysia– Schedular Tax Deduction Scheme Second Edition is an improved version that includes current changes in the scheme structure of 2009. A topic on Self Assessment System (SAS) is added so as to help employers and individual taxpayers in comprehending their responsibilities as well as helping the employers in managing tax payments for their employees. The Schedular Tax Deduction (STD) scheme is the main focus under the Self Assessment System in order to settle the tax payment to the Inland Revenue Board (IRB), thus a better understanding on the system is crucial. The content of this book is based on the implementation by IRBM through the provision of Statement of Tax Deductions under Income Tax (Deduction from Remunerations) Rules 1994 [DFR 1994]. Most examples shown in this book are based on examples provided by IRB for 2009 to ensure that readers are able to easily understand the effort done by them. Examples on calculations of the amount that must be deducted under the STD scheme is also included apart from the brief explanation on the application of eCP39 and STD software program issued by the IRB.